Optimization, and Evaluation of Hyaluronic Acid Conjugated PLGA Nanoparticles of Etoposide for Cancer Treatment - Paswan, Suresh Kumar (Asian Journal of Pharmaceutics (AJP), 2023)
Introduction: Etoposide is used for the treatment of small-lung cancer. It is associated with the major side effect of secondary leukemia. Targeting of formulation subdues the side effects associated with etoposide making it safer for use. The current work aims to prepare and evaluate etoposide-loaded poly (lactic-co-glycolic acid)-polyethylene glycol hyaluronic acid (PLGA-PEG-HA) nanoparticles to deliver etoposide to lung cancer cells by active targeting of the CD44 receptor. Materials and Methods: Nanoparticles were prepared using the emulsification solvent evaporation technique and Box-Behnken design was employed to optimize the formulation, and the effect of independent variables, that is, PLGA-PEG-HA, Polyvinyl alcohol solution, etoposide on formulation was analyzed. Scanning electron microscopy, differential scanning calorimetry, X-ray diffraction, and in vitro drug release studies were used to evaluate etoposide-loaded PLGA-PEG-HA nanoparticles. The cytotoxicity of the formulation on the A549 cell line was to evaluate the mortality rate of cancer cells. Results and Discussion: The average particle size, poly-dispersibility index, zeta potential, and entrapment efficiency were 283.35 nm, 0.57, −8.70 nm, and 53.21%, respectively. The optimized batch showed 10.69% immediate release and 6 h sustained release and the drug release pattern followed the Korsmeyer- Peppas model. In the cell line study, the formulation showed a cell mortality rate of 72.14% and an IC50 value of 2 μM. Conclusion: Etoposide-loaded PLGA-PEG-HA nanoparticles for targeted delivery of etoposide to lung cancer cells were successfully prepared. The results showed that etoposide-loaded PLGA-PEG-HA nanoparticles have significantly increased cell death at concentrations considerably lower than those of free etoposide. It will reduce the overall dose required and improve the safety of treatment, which could ultimately lead to better outcomes for patients.